1991
DOI: 10.1177/095632029100200306
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity against VZV and HSV Type 1 and Type 2 of the (+) and (−) Enantiomers of (R,S)-9-[4-hydroxy-2-(hydroxymethyl)butyl]guanine, in Comparison to other Closely Related Acyclic Nucleosides

Abstract: The separate (+) and (−) enantiomers of the acyclic guanosine analogue 9-[4-hydroxy-2-(hydroxymethyl)-butyl]guanine (2HM-HBG) were tested for inhibition of varicella-zoster virus (VZV), herpes simplex virus type 1 (HSV-1) and herpes simplex virus type 2 (HSV-2). In all cases the (−) enantiomer was the most active enantiomer. The (+) enantiomer was 10 times less active than the racemate against VZV and inactive against HSV-1 and -2. The parent compound, 9-(4-hydroxybutyl)guanine, containing an unbranched side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The (+)enantiomer of H2G at 3x10 mg kg-1 day-1 did not show any inhibition of SIV sm replication in monkeys (Fig. 2a) in agreement with the earlier observation that the (-)enantiomer was more inhibitory than the (+)enantiomer to HSV, VZV (Abele et al, 1991) and HHV-6 replication (Akesson- Johansson et al, 1990). The enantiomeric mixture (±)H2G at 3x25 mg kg-1 day-1 was inhibitory (Fig.…”
Section: Toxicity Evaluationsupporting
confidence: 79%
See 1 more Smart Citation
“…The (+)enantiomer of H2G at 3x10 mg kg-1 day-1 did not show any inhibition of SIV sm replication in monkeys (Fig. 2a) in agreement with the earlier observation that the (-)enantiomer was more inhibitory than the (+)enantiomer to HSV, VZV (Abele et al, 1991) and HHV-6 replication (Akesson- Johansson et al, 1990). The enantiomeric mixture (±)H2G at 3x25 mg kg-1 day-1 was inhibitory (Fig.…”
Section: Toxicity Evaluationsupporting
confidence: 79%
“…It was also observed that H2G and (±)H2G were not active against thymidine kinase negative HSV or VZV variants (Larsson et al, 1986;Abele et al, 1991). Surprisingly, in view of the fact that lentiviruses lack viral thymidine kinase, variable antiviral effect at 2->100 IlM of H2G and (±)H2G was found in different cells infected with HIV-1, HIV-2 and SIV sm' The variability was seen in all types of cells and for all viruses tested when the assays were repeated several times.…”
Section: Toxicity Evaluationmentioning
confidence: 90%
“…H2G showed a potency similar to that of ACV against HSV-1, but less potency against HSV-2. Previous studies done on TK-deficient VZV strains indicated that a functional viral TK was necessary in order to achieve the potent antiviral effect seen with H2G in vitro (1). In this study, we tested a TK-deficient HSV-1 mutant, HSV-1(F)⌬305, which has a genetically engineered deletion in the viral TK gene (21).…”
Section: Antiviral Activity Of H2g Against Herpesviruses In Vitromentioning
confidence: 99%
“…(R)-9-[4-Hydroxy-2-(hydroxymethy)butyl]guanine (H2G; USAN, omaciclovir) is a nucleoside analog with in vitro inhibitory activity against VZV, herpes simplex virus types 1 and 2 (HSV-1 and -2), Epstein-Barr virus, and human herpesvirus 6 (1,4,5,15). It is more active against VZV than the currently approved agents, ACV and penciclovir (PCV) (1,5,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation